2015
DOI: 10.1016/j.cellsig.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 can feedback-regulate cellular MEK1/2 levels

Abstract: Signal transduction of the Raf/MEK/ERK pathway is regulated by various feedback mechanisms. Given the greater molar ratio between Raf-MEK than between MEK-ERK in cells, it may be possible that MEK1/2 levels are regulated to modulate Raf/MEK/ERK activity upon pathway stimulation. Nevertheless, it has not been reported whether MEK1/2 expression can be subject to a feedback regulation. Here, we report that the Raf/MEK/ERK pathway can feedback-regulate cellular MEK1 and MEK2 levels. In different cell types, ΔRaf-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Moreover, we previously demonstrated that although MEK1 levels are mildly upregulated under conditions of mortalin depletion (Fig. 6, bottom panel), this is mainly due to MEK1 transcription upregulated via an ERK1/2-mediated feedback loop, which is activated by mortalin depletion (48). Of note, a recent report has demonstrated that HSP70 can also regulate the stability of folded proteins via a mechanism wherein its lid and substrate- , and PP1␥ in melanoma and pancreatic ductal adenocarcinoma patient biopsy specimens determined by the copy number analysis algorithms defined by genomic identification of significant targets in cancer (GISTIC) (63) and RAE (64).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we previously demonstrated that although MEK1 levels are mildly upregulated under conditions of mortalin depletion (Fig. 6, bottom panel), this is mainly due to MEK1 transcription upregulated via an ERK1/2-mediated feedback loop, which is activated by mortalin depletion (48). Of note, a recent report has demonstrated that HSP70 can also regulate the stability of folded proteins via a mechanism wherein its lid and substrate- , and PP1␥ in melanoma and pancreatic ductal adenocarcinoma patient biopsy specimens determined by the copy number analysis algorithms defined by genomic identification of significant targets in cancer (GISTIC) (63) and RAE (64).…”
Section: Discussionmentioning
confidence: 99%
“…ERK phosphorylates numerous substrates in the cytoplasm and nucleus that play a role in cell fate, such as RSK and the AP‐1 and ETS families of transcription factors. (B) The ERK pathway has many intrinsic mechanisms of negative feedback regulation . ERK can exert negative feedback at each level of the pathway via phosphoregulation.…”
Section: Overview Of the Erk Signaling Pathwaymentioning
confidence: 99%
“…ERK can exert negative feedback at each level of the pathway via phosphoregulation. ERK can also drive transcription of negative pathway regulators such as DUSP5/6 and SPRY that can and inactivate members of the ERK pathway . Abbreviations: AP‐1, activating protein‐1; ERK, extracellular signal‐regulated kinase; DUSP, dual specificity phosphatase; Grb, growth factor receptor‐bound protein; MEK, mitogen‐activated protein kinase/ERK kinase; RSK, ribosomal s6 kinase; RTK, receptor tyrosine kinase; SOS, Son of Sevenless homolog; SPRY, sprouty homolog [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Overview Of the Erk Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations